2014
DOI: 10.1002/ijc.28957
|View full text |Cite
|
Sign up to set email alerts
|

Delayed apoptosis of tumor associated neutrophils in the absence of endogenous IFN‐β

Abstract: The importance of neutrophils in tumor immune surveillance, invasive growth and angiogenesis becomes increasingly clear. Many of neutrophil activities are controlled by endogenous IFN-b. Here, we provide evidence that endogenous IFN-b is regulating the apoptosis of pro-angiogenic tumor infiltrating neutrophils by influencing both, the extrinsic as well as the intrinsic apoptosis pathways. Accordingly, the life span of tumor associated neutrophils (TANs) is remarkably prolonged in tumor bearing Ifnb1 2/2 mice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 49 publications
(69 reference statements)
9
69
0
1
Order By: Relevance
“…Interestingly, it has been proposed that there can be phenotypic or functional plasticity, where neutrophils infiltrating a tumor are modulated by cues present in the tumor environment. 23 This has been well exemplified by recent works showing that TANs can be modulated and polarized toward an N1 phenotype by type-1 interferons [24][25][26] or a pro-tumorigenic (N2) phenotype by the presence of TGFb 7 as demonstrated by the observation that systemic inhibition of TGFb using a specific Alk5 kinase inhibitor called SM16 in mice caused a shift toward a pro-inflammatory and antitumor phenotype (N1).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, it has been proposed that there can be phenotypic or functional plasticity, where neutrophils infiltrating a tumor are modulated by cues present in the tumor environment. 23 This has been well exemplified by recent works showing that TANs can be modulated and polarized toward an N1 phenotype by type-1 interferons [24][25][26] or a pro-tumorigenic (N2) phenotype by the presence of TGFb 7 as demonstrated by the observation that systemic inhibition of TGFb using a specific Alk5 kinase inhibitor called SM16 in mice caused a shift toward a pro-inflammatory and antitumor phenotype (N1).…”
Section: Introductionmentioning
confidence: 94%
“…7 In contrast, in the presence of type-I IFNs or absence of TGFb, TANs display an antitumor N1 phenotype with increased tumor cytotoxicity, high neutrophil extracellular traps (NETs) expression, high ICAM1, and TNF-a expression. 9,24,26 Using transcriptomic analysis 29 , we have previously shown that N2-polarized TANs display a dramatically different transcriptomic profile than both myeloid-derived suppressor cells (G-MDSCs) and naive bone marrow neutrophils (BMN), including the expression of a wide range of cytokines (CCL17, CCL2, CCL5). By secreting CCL17, TANs were further shown to recruit regulatory T-cells to the tumor site, thus inducing immunologic self-tolerance and impaired immune response to tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon, together with the enhanced infiltration of lungs by these cells, leads to improved metastatic load in IFN-deficient mice (20). N2 neutrophils are characterized with immature nucleus shape and reduced tumor cell killing capacity (34); they were also shown to recruit regulatory T cells in tumors by expression of CCL17 (35). Accordingly, in clinical studies, the percentage of neutrophils in blood and neutrophil/lymphocyte ratio was shown to be negative predictors of patient outcome in different types of cancer (36, 37).…”
Section: Tumor Microenvironment and The Phenotype Of Neutrophilsmentioning
confidence: 99%
“…The researchers concluded that adaptive immune cells are not involved in the IFNβ-dependent inhibition of tumor angiogenesis by repeating the experiments in Ifnb1 −/− Rag2 −/− and Rag2 −/− mice that lack T and B-cells [103, 105]. Moreover, in the Ifnb1 −/− mice model deficiency of IFNβ delays the apoptosis of pro-angiogenic neutrophils infiltrating the tumor [106]. …”
Section: Tumor Progressionmentioning
confidence: 99%